الادارة الالكترونية في النظامين المغربي والجزائري_ دراسة مقارنة - بورزقة, صفاء; قاسم, ميلود (University of Eloued جامعة الوادي, 2021)
اصبح تبني مشروع الادارة الالكترونية ضرورة ملحة للارتقاء باداء الجهاز الاداري وتقريبه من المواطن، فرضتها الثورة المعلوماتية التي كان لها تأثير مباشر على مختلف دول العالم بدرجات متفاوتة ، وقد كان للانظمة الادارية العربية النصيب الكافي من هذا التاثير حيث سعت هي الاخرى لاعتماد الادارة الالكترونية في تسيير الادارة العمومية وكانت المغرب والجزائر من بين الدول التي بادرت بكل الاليات والبرامج لتبني الادارة الالكترونية في ظل تغييرات البيئة السياسية والاقتصادية والتي كان لها التاثير المباشر في فعالية وكفاءة تحقيق اهدافها .لذا تناولنا في البحث تطبيقات الادارة الالكترونية في ظل تاثيرات البيئة السياسية والاقتصادية في الجزائر والمغرب بمنظور مقارن باستعراض اهم منجزاتها في هذا المجال ومدى فعاليتها في تحقيق الاهداف المرجوة منها. The E- administration adoption has become a pressing need for the administration performance improvement and for moving more closer to the citizen, which is imposed by the information technology revolution that had a direct effect on several countries in divergent degrees. In this context, the administration systems of the Arab states had an adequate share of these effects what induced them also sought to adopt the E-administration. Among these countries, Algeria and Morocco have been firmly committed to adopting E-administration through several mechanisms and programs, especially in the light of economic and political environment changes, which have a direct impact on performance and effectiveness in achieving its objectives. Therefore, in this paper, we examine the economic and political environment effects on the E-administration applications in Algeria and Morocco from a comparative view by showing the most significant achievements in this realm and the extent they achieve their goals effectively.
مجلد12، عدد1
Keywords: البيروقراطية ; الادارة الالكترونية ; المواطن ; المغرب ; الجزائر; Bureaucracy ; E-administration; citizen ; Morocco ; Algeria